Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Puskesmas Panca Makmur Kecamatan Soyojaya Kabupaten Morowali Utara - Ratnasari, Dwi; Kornelius, Yoberth; Indriani Ibrahim, Andi; Risky Islianty, Nur (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of motivation and work environment on employee performance at Panca Makmur Community Health Center, Soyo Jaya District, North Morowali Regency. The objective was to analyze the partial and simultaneous effects of both variables on performance. This research used a quantitative associative approach with a sample of 50 employees. Data were analyzed using multiple linear regression. The results show that motivation had no significant partial effect, while the work environment had a positive and significant effect. Simultaneously, both variables significantly affected employee performance. These findings highlight the importance of a supportive work environment in improving performance. Keywords: motivation, work environment, employee performance, community health center, quantitative study, regression analysis, public service